Recomendaciones CODEPEH 2014 - Faustino Núñez Batalla; Carmen Jáudenes Casaubón; Jose Miguel Sequí Canet; Ana Vivanco Allende; José Zubicaray Ugarteche (Revista Española de Discapacidad, 2015)
Núñez, F. et al. (2015): “Recomendaciones CODEPEH 2014”, Revista Española de Discapacidad, 3 (1): 163-186.